Blast resistance of tuff stone masonry walls. (15th April 2016) - Parisi, Fulvio; Balestrieri, Claudio; Asprone, Domenico
Highlights: Investigation on blast resistance of tuff stone masonry walls. Dynamic analysis under triangular pressure time-histories. Derivation of pressure–impulse diagrams for design and assessment. Sensitivity to modelling options, vertical pre-compression and aspect ratio. Comparison with analytical methods, code pressures and real pressures of incidents. Abstract: Gas explosions frequently occur in residential buildings inducing the out-of-plane collapse of single structural components which may trigger the progressive collapse of the structure. In this study, the out-of-plane collapse capacity of load-bearing tuff stone masonry (TSM) walls subjected to blast loading is investigated. A finite element macro-modelling strategy was adopted and dynamic analysis was carried out through LS-DYNA software to derive pressure–impulse diagrams for blast resistant design and assessment. Different modelling assumptions were considered. A sensitivity analysis allowed the evaluation of the influence of vertical pre-compression level and aspect ratio of TSM walls on blast collapse capacity. Numerical predictions of blast capacity were then compared to those provided by simplified analytical models, design code pressures and peak pressures estimated after real incidents.